Duplications in ADHD patients harbour neurobehavioural genes that are co‐expressed with genes associated with hyperactivity in the mouse. Issue 2 (5th February 2015) - Taylor, Avigail; Steinberg, Julia; Webber, Caleb
Abstract : Attention deficit/hyperactivity disorder (ADHD) is a childhood onset disorder, prevalent in 5.3% of children and 1–4% of adults. ADHD is highly heritable, with a burden of large (>500 Kb) copy number variants (CNVs) identified among individuals with ADHD. However, how such CNVs exert their effects is poorly understood. We examined the genes affected by 71 large, rare, and predominantly inherited CNVs identified among 902 individuals with ADHD. We applied both mouse‐knockout functional enrichment analyses, exploiting behavioral phenotypes arising from the determined disruption of 1:1 mouse orthologues, and human brain‐specific spatio‐temporal expression data to uncover molecular pathways common among genes contributing to enriched phenotypes. Twenty‐two percent of genes duplicated in individuals with ADHD that had mouse phenotypic information were associated with abnormal learning/memory/conditioning (" l/m/c ") phenotypes. Although not observed in a second ADHD‐cohort, we identified a similar enrichment among genes duplicated by eight de novo CNVs present in eight individuals with Hyperactivity and/or Short attention span (" Hyperactivity/SAS ", the ontologically‐derived phenotypic components of ADHD). In the brain, genes duplicated in patients with ADHD and Hyperactivity/SAS and whose orthologues' disruption yields l/m/c phenotypes in mouse ("candidate‐genes"), were co‐expressed with one another and with genes whose orthologues' mouse models exhibit hyperactivity. Moreover, genes associated with hyperactivity in the mouse were significantly more co‐expressed with ADHD candidate‐genes than with similarly identified genes from individuals with intellectual disability. Our findings support an etiology for ADHD distinct from intellectual disability, and mechanistically related to genes associated with hyperactivity phenotypes in other mammalian species. © 2015 Wiley Periodicals, Inc.